"The Last Block of Ice": Trauma Literature in the High School Classroom. Issue 2 (17th June 2017) - Moore, Amber; Begoray, Deborah
Abstract: This article explores the potential of using trauma literature in the secondary high school classroom, drawing from a case study that explored grade 10 secondary students' responses to a trauma story. These responses were primarily collected from their digital writing and reveal a number of interesting findings, including the expression of anger and aggression in their writing, discussions of combating depression, and engaging in supportive communication. In addition, some students did not address some expected topics, so there were some interesting silences that emerged in the study.